Principles in practice: an examination of cascading. (2nd August 2019) - Heaver, Trevor D.
This article examines the concept of cascading of container ships and the relationship of cascading to fleet management. It is written to apply two of the legacies that Richard Goss left to the maritime community: discussion of maritime topics through conferences and journals; and the application of basic economic principles to shipping. Richard had a special interest in the many aspects of the economics of ship size. The increases in the size of container vessels on the East Asia to Northwest Europe route since 2000 gives rise to the type of concept that Richard might have examined; the cascading of ships. The concept of cascading is examined in the light of basic aspects of the economics of ships size. It is shown that cascading does not take place simply because of the displacement of large vessels from certain routes but is dependent on the presence of various dynamic forces affecting the fleet deployment decisions of lines. Cascading is shown to be a process guided by management decisions affected by financial as well as economic considerations. It is not as simple as water running downhill.